2005
DOI: 10.1007/s11270-005-5268-5
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Source of Heavy Metal Contamination in Sediments of Gomti River (India) using Principal Component Analysis

Abstract: This study explores the extent and possible sources of heavy metal (Cd, Cr, Cu, Fe, Mn, Pb, Zn and Ni) contamination in the bed sediments of the Gomti River performing principal component analysis on the five years (Jan. 1994-Dec. 1998) data set obtained through continuous monitoring of the river water and bed sediments at eight selected sites and water/wastewater of its tributaries/drains. Influence of anthropogenic activities on metal contamination of the bed sediments was evaluated through computing the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(109 citation statements)
references
References 25 publications
4
96
1
1
Order By: Relevance
“…The PCA was performed using varimax normalized rotation on the dataset, and the CA was applied to the standardized matrix of the samples using Ward's method, and the results are reported in the form of dendrograms. PCA and CA complement each other and have been widely used in environmental studies (Gielar et al 2012;Iqbal and Shah 2011;Shah et al 2012;Singh et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCA was performed using varimax normalized rotation on the dataset, and the CA was applied to the standardized matrix of the samples using Ward's method, and the results are reported in the form of dendrograms. PCA and CA complement each other and have been widely used in environmental studies (Gielar et al 2012;Iqbal and Shah 2011;Shah et al 2012;Singh et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Sediments are ecologically sensitive components of the aquatic ecosystems and are also a reservoir of the contaminants, which take part considerably in maintaining the trophic status for any water reservoir (Singh et al 2005). Depending upon the physicochemical conditions, sediments can act both as source and sink for nutrients and heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al, (2005) and Gaur et. al, (2005) also resulted in their study that the Gomti river sediments are in unpolluted from the Fe, Cu, Cd, Mn were in case of other metal Pb its recorded partially to moderate polluted.…”
Section: Index Of Geo Accumulationmentioning
confidence: 92%
“…It was noted that the site Sitapur over bridge is least polluted in all the season in all the three years (Table 1-6). Singh et al, (2005) (Table 5), maximum value of Cu was observed at site Dilkusha rail over bridge, whereas in post-monsoon season it was found high at site Dilkusha 32.11 µg g -1 and range was observed between 32.11 13.94 µg g -1 (Table 6). By comparing the guideline for contaminated fresh water sediments (US EPA, 1977) its concluded that site Hanuman setu, Laxaman mela park, Saheed park and Dilkusha were found moderate polluted at most of the sampling time while in term of As and Fe it was found low polluted to unpolluted.…”
Section: Iron (Fe)mentioning
confidence: 94%
“…PCA of the normalized variables was performed to extract significant PCs and to further reduce the contribution of variables with minor significance; these PCs were subjected to varimax rotation with Kaiser Normalization generating VFs (Brumelis et al 2000;Singh et al 2004Singh et al , 2005aLove et al 2004;Abdul-Wahab et al 2005). The factor analysis can be shown by the following equation:…”
Section: Pca and Famentioning
confidence: 99%